Delivery systems for astaxanthin: A review on approaches for in situ dosage in the treatment of inflammation associated diseases - Rivera-Hernández, Gabriela; Roether, Judith; Aquino, Carolina; Boccaccini, Aldo R.; Sánchez, Mirna L. (International Journal of Pharmaceutics, 2025)
Astaxanthin is a red–orange keto-carotenoid exhibiting antioxidant activity. AST is mainly used in the cosmetic, food, and healthcare industries. Nevertheless, because of its anti-inflammatory effects and immune modulation activity, AST use in pharmacology has been proposed as an alternative for treating neurodegenerative disorders, inflammatory bowel disease, arthritis, atherosclerosis, or diabetic foot ulcers, among others. However, before an AST clinical implementation, it is still necessary to solve challenges related to the use of AST, such as lack of solubility, poor bioavailability, and sensitivity to light, oxygen, and temperature. For that reason, the development of several biomaterials to encapsulate, protect, and dosage AST has been proposed in recent years. This review discusses the use of liposomes, hydrogels, and polymer micro and nanoparticles as vehicles for AST release based on available literature. Additionally, an analysis of released, encapsulated, and effective AST doses is presented, as well as the regulatory landscape of different delivery systems to reveal details of AST delivery, which should inform future strategies for implementing AST in the clinic.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Astaxanthin; Chronic inflamation disease; Drug delivery; Hydrogels; Microparticles; Nanoparticles; Wound healing